UMP embarks on 6R Campaign for sustainable green campus - Mohd Marzuki, Mohamed (2019)
Universiti Malaysia Pahang (UMP) has recently embarked on its Green Policy, and launched the “Let’s Break Up with Single-Use Plastic” campaign on February 19, 2019, at its Sports Complex, Gambang Campus, to encourage students and faculty members alike to reduce the usage of plastics.